Rural Health: Agriculture, Pesticides and Organic Dusts 2018
DOI: 10.1136/oemed-2018-icohabstracts.1360
|View full text |Cite
|
Sign up to set email alerts
|

1293 Knowledge, attitudes, and practices of the user gardeners of pesticides in burkina faso

Abstract: IntroductionPesticides are very useful in the field of gardening for the fight against pests, which exposes gardeners to the risks associated with their use. The aim of our work was to study the incurred risks by the gardeners in Ouagadougou, to bring them to adhere to the prevention strategies implemented for their health and safety.MethodsIt was a descriptive and cross-sectional study. The study population consisted of 101 gardeners coming from three districts. They were involved in a no probabilistic way by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, it has been reported that the risk of hypertension is twice as high if it is associated with a psychological work environment combining high psychological demands and low decision latitude (Taleb et al, 2003). Respectively among staff serving refugees, and asylum seekers in Dakar and among workers of an insurance company in Benin, occupational stress prevalences of 40.38% and 80.8% were estimated (Dia et al, 2018;Hinson et al, 2017). Like in other developing countries, the phenomenon of occupational stress in Burkina Faso is a reality but is not well-known to employees, nor are the of work-related illnesses and accidents.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, it has been reported that the risk of hypertension is twice as high if it is associated with a psychological work environment combining high psychological demands and low decision latitude (Taleb et al, 2003). Respectively among staff serving refugees, and asylum seekers in Dakar and among workers of an insurance company in Benin, occupational stress prevalences of 40.38% and 80.8% were estimated (Dia et al, 2018;Hinson et al, 2017). Like in other developing countries, the phenomenon of occupational stress in Burkina Faso is a reality but is not well-known to employees, nor are the of work-related illnesses and accidents.…”
Section: Introductionmentioning
confidence: 95%